eta-paired superconducting hidden phase in photodoped Mott insulators - Li, Jiajun; Golez, Denis; Werner, Philipp; Eckstein, Martin (Physical Review B, 2020)
We show that a metastable eta-pairing superconducting phase can be induced by photodoping doublons and holes into a strongly repulsive fermionic Hubbard model. The doublon-hole condensate originates from an intrinsic doublon-hole exchange interaction and does not rely on the symmetry of the half-filled Hubbard model. It extends over a wide range of doublon densities and effective temperatures. Different nonequilibrium protocols to realize this state are proposed and numerically tested. We also study the optical conductivity in the superconducting phase, which exhibits ideal metallic behavior, i.e., a delta function at zero frequency in the conductivity, in conjunction with a negative conductivity at large frequencies. These characteristic optical properties can provide a fingerprint of the eta-pairing phase in pump-probe experiments.
CRIS-Team WoS Importer:2020-11-06